Consumer response towards stall-free pork premiums at the restaurant level - Eden, Michaela Ann (Kansas State University, 2021)
Over time, consumer preference towards agriculture has changed. These changes include concerns about livestock production. In the pork industry, the use of gestation stalls has been a reoccurring topic for stakeholders. Gestation stalls are two-foot by seven-foot stalls housing gestating, or pregnant, sows. These stalls are regularly used in the pork-producing industry; however, many consumers have developed concern towards the limited mobility these stalls provide. To address these concerns, some U.S. states have implemented bans on gestation stalls, passed via ballot initiative or legislation. The process producers must go through to meet these improved welfare standards is capital-intensive. Improved welfare standards are an example of credence attributes, or attributes that are immeasurable by taste or physical appearance. Previous studies have addressed premiums at the retail or grocery store level and few at the restaurant level. The aim of this thesis is to identify consumer responses towards premiums on gestation stall-free meal at the restaurant level. A survey was used to determine consumer preferences of purchasing a pork chop meal at a restaurant that sources pork from a place that is voluntarily using stall-free housing at different premium levels ($0, $2, $4, $6). Using a discrete binary logistic regression, we estimate the predicted probability of a consumer choosing a stall-free pork chop meal at the different premium levels. Our results show that as premiums increase, people are less likely to choose the stall-free meal. To target 50% of the population who will choose the stall-free restaurant meal, we expect the market may support premiums of up to $3.50 more for a meal that is stall-free.
Keywords: Consumer preference; Pork; Gestation stalls; Stall-free restaurant meal